2019
DOI: 10.1093/cid/ciz581
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Follow-up of Active Tuberculosis Development From Latent Infection in Rural China

Abstract: A 5-year follow-up study found declining disease development rates from latent tuberculosis infection. In the latter 3 years, the incidence, per 100 person-years, was 0.26 for interferon-γ release assay positives and 0.19 for tuberculin skin test positives (P = .28). In addition, all round have been checked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In the present study, we detected increased proportions of positive IGRA results and high OR values in children with household or non-household contact risk. Population-based multicenter studies performed in China have revealed that individuals with baseline results of IGRA+ /TST− showed a similar or higher incidence of active TB than those with baseline results IGRA+/TST+ or IGRA− /TST+ , either within the first 2 years of follow-up [ 12 ] or 5 years of follow-up [ 13 ]. Data from in our study which showed that discordance favored IGRA+/TST− in those with active TB whereas among those without active TB discordance favors TST+/IGRA−, suggested higher sensitivity and specificity of IGRA than that of TST.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we detected increased proportions of positive IGRA results and high OR values in children with household or non-household contact risk. Population-based multicenter studies performed in China have revealed that individuals with baseline results of IGRA+ /TST− showed a similar or higher incidence of active TB than those with baseline results IGRA+/TST+ or IGRA− /TST+ , either within the first 2 years of follow-up [ 12 ] or 5 years of follow-up [ 13 ]. Data from in our study which showed that discordance favored IGRA+/TST− in those with active TB whereas among those without active TB discordance favors TST+/IGRA−, suggested higher sensitivity and specificity of IGRA than that of TST.…”
Section: Discussionmentioning
confidence: 99%
“…Most subjects suffered with MTB infection stay clinically asymptomatic which is called latent TB infection (LTBI). A relatively small proportion of these individuals would develop to active TB (ATB) during their life ( 3 , 4 ). TB control strategies largely focus on identification and treatment of people with ATB.…”
Section: Introductionmentioning
confidence: 99%
“…TB remains an important infectious disease worldwide ( Haas et al., 2016 ; Furin et al., 2019 ). To achieve TB elimination strategy, rapid, inexpensive, and accurate methods for differentiating between ATB and LTBI are urgently required, especially in high-endemic countries such as China ( World Health Organization, 2016 ; Gao et al., 2017 ; Xin et al., 2019 ). The conventional pathogen-detecting methods have limitations in clinical application ( MacLean et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%